Solidarity and Implications of a Leaderless Movement in Hong Kong: Its Strengths and Limitations - LAI, YAN-HO; SING, MING (Communist and post-communist studies, 2020)
In 2019, what began in Hong Kong as a series of rallies against a proposal to permit extraditions to mainland China grew into a raft of anti-authoritarian protests and challenges to Beijing’s grip on the city. Given the gravest political crisis confronting Hong Kong in decades, this research investigates why the protests have lacked centralized leaders and why the solidarity among the peaceful and militant protesters has been immense. This article also examines the strengths and limitations of this leaderless movement with different case studies. The authors argue that serious threats to the commonly cherished values in Hong Kong, amid the absence of stable and legitimate leaders in its democracy movement, underpinned the formation of a multitude of decentralized decision-making platforms that orchestrated the protests in 2019. Those platforms involved both wellknown movement leaders organizing conventional peaceful protests and anonymous activists crafting a diversity of tactics in ingenious ways, ranging from economic boycotts, human chains around the city, artistic protests via Lennon Walls, to the occupying of the international airport. The decentralized decisionmaking platforms, while having generated a boon to the movement with their beneficial tactical division of labor, also produced risks to the campaign. The risks include the lack of legitimate representatives for conflict-deescalating negotiations, rise in legitimacy-sapping violence, and susceptibility to underestimating the risks of various tactics stemming from a dearth of thorough political communication among anonymous participants who had different goals and degrees of risk tolerance. In short, Hong Kong’s anti-extradition movement in 2019 sheds light on the basis of leaderless movements, and on both the strengths and risks of such movements.